Modern development trends in high-performance soft ferrites - Žnidaršič, Andrej (Informacije MIDEM, 2002)
This paper considers the current MnZn-ferrite development trends in high-performance soft ferrites. Today, soft ferrites play the dominant role in magnetic materials. They are produced in large quantities in a wide variety of applications. As a result, research and development in both industry and research centres has made great efforts to develope new classes of soft-ferrite materials.
Keywords: električne lastnosti; feriti; magnetna keramika; magnetne lastnosti; mikrostruktura